A lightweight front plate for photovoltaic modules and its preparation method and application
By using acrylic resin and organic flash powder lamination technology in photovoltaic modules, a lightweight front panel was prepared, which solved the problem of single appearance and photoelectric efficiency of traditional photovoltaic modules, and achieved the balance of multi-color selection and efficient power generation.
Patent Information
- Application Number
- CN202411487263.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The front panel of traditional photovoltaic modules is usually single-color glass, which limits the appearance design and application scenarios of photovoltaic modules. Changing the cell preparation process to change the appearance color may affect the photoelectric conversion efficiency.
By mixing and extruding acrylic resin, curing agent and additives, an extruded resin is obtained and laminated with organic flash powder to prepare a lightweight front panel of photovoltaic modules, achieving a variety of colors without affecting light transmittance and Photoelectric conversion efficiency.
It realizes changing the appearance color of the photovoltaic module without affecting the light transmittance and photoelectric conversion efficiency of the photovoltaic module, providing a richer appearance choice, meeting different customer needs, and improving the stability and weather resistance of the module.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional materials, and in particular to a lightweight front plate of a photovoltaic module and a preparation method and application thereof. Background Art
[0002] As the global demand for renewable energy grows, photovoltaic power generation has been widely used as a clean and efficient energy source. Photovoltaic modules are the core part of photovoltaic power generation systems. They are mainly composed of front panels, cells, back panels and adhesive films. The main function of the front panel is to protect the cells and prevent damage to the cells by external environmental factors, while ensuring that the cells can fully absorb sunlight. However, traditional photovoltaic modules mainly use glass as the front panel, usually in a single color, such as blue or black, which to a certain extent limits the appearance design and application scenarios of photovoltaic modules.
[0003] In order to solve the above problems, the existing technology mainly changes the manufacturing process of the cell to make it emit light of different colors, thereby changing the appearance color of the photovoltaic module. However, changing the manufacturing process of the cell may affect the photoelectric conversion efficiency of the cell, thereby reducing the power generation efficiency of the photovoltaic module. Summary of the invention
[0004] The purpose of the present invention is to provide a lightweight front plate of a photovoltaic module and a preparation method and application thereof. The lightweight front plate of the photovoltaic module provided by the present invention can change the appearance color of the photovoltaic module without affecting the light transmittance and photoelectric conversion efficiency of the photovoltaic module.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a lightweight front plate of a photovoltaic module, comprising the following steps:
[0007] The acrylic resin, the curing agent and the auxiliary agent are mixed and extruded to obtain an extruded resin;
[0008] The extruded resin is mixed with organic flash powder for lamination to obtain the lightweight front plate of the photovoltaic module.
[0009] Preferably, the mass of the organic flash powder is 0.1-2.5% of the mass of the extruded resin.
[0010] Preferably, the organic glitter powder includes T80-607 and / or T80-134.
[0011] Preferably, the lamination temperature is 130-180° C., the pressure is 0.1-1 MPa, and the heat preservation and pressure holding time is 30-60 min.
[0012] Preferably, the mass ratio of the acrylic resin, the curing agent and the auxiliary agent is 70-76:19-23:1-5.
[0013] Preferably, the acrylic resin comprises the following raw materials in parts by weight: 30-60 parts of methyl methacrylate, 10-20 parts of n-butyl acrylate, 10-30 parts of glycidyl methacrylate, 5-15 parts of styrene, 1-4 parts of chain transfer agent, 1-5 parts of initiator, and 30-50 parts of solvent.
[0014] Preferably, the chain transfer agent is aliphatic thiol and / or dithioester; and the initiator is a peroxide initiator.
[0015] Preferably, the extrusion temperature is 50-110° C., and the main machine speed is 40-200 rpm.
[0016] The present invention provides a lightweight front plate of a photovoltaic module prepared by the preparation method described in the above technical solution.
[0017] The present invention provides the application of the lightweight front plate of the photovoltaic module described in the above technical solution in solar photovoltaic power generation.
[0018] The present invention provides a method for preparing a lightweight front plate of a photovoltaic module, comprising the following steps: mixing an acrylic resin, a curing agent and an auxiliary agent for extrusion to obtain an extruded resin; mixing the extruded resin with an organic flash powder for lamination to obtain the lightweight front plate of the photovoltaic module. The present invention mixes an acrylic resin, a curing agent and an auxiliary agent for extrusion, and the obtained extruded resin is used as a base material, which is convenient for forming a lightweight front plate with a variety of colors by adding different organic flash powders, which can not only provide a richer and more diverse selection of photovoltaic module appearance colors to meet the needs of different customers, but also the present invention adopts lamination technology to prepare the lightweight front plate of the photovoltaic module, which can change the appearance color of the photovoltaic module without affecting the light transmittance and photoelectric conversion efficiency of the photovoltaic module, and can also make the lightweight front plate of the photovoltaic module have good stability and weather resistance, thereby ensuring the stability and reliability of the photovoltaic module during long-term use. In addition, the method for preparing the lightweight front plate of the photovoltaic module in the present invention is simple and easy to operate, low in cost, and can achieve the change of the color of the photovoltaic module without changing the preparation process of the battery cell, solving the problems of complex process and high cost that may exist in the related art due to changing the preparation process of the battery cell.
[0019] Furthermore, the present invention facilitates precise control of the appearance color of photovoltaic modules by adjusting the type and proportion of organic flash powder, thereby meeting the needs of different customers; at the same time, an ideal surface effect can be created according to customer needs, so that the photovoltaic modules not only have a power generation function, but also a decorative function, thereby improving the overall aesthetics of the building. DETAILED DESCRIPTION
[0020] The present invention provides a method for preparing a lightweight front plate of a photovoltaic module, comprising the following steps:
[0021] The acrylic resin, the curing agent and the auxiliary agent are mixed and extruded to obtain an extruded resin;
[0022] The extruded resin is mixed with organic flash powder for lamination to obtain the lightweight front plate of the photovoltaic module.
[0023] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.
[0024] The present invention mixes acrylic resin, curing agent and auxiliary agent and extrude them to obtain extruded resin. In an embodiment of the present invention, the mass ratio of the acrylic resin, curing agent and auxiliary agent can be 70-76:19-23:1-5, further can be 73-75:20-21:2-4, specifically can be 74:20.5:3. Firstly, the raw materials and preparation method of the acrylic resin of the present invention are described in detail.
[0025] In an embodiment of the present invention, the acrylic resin may include the following raw materials in parts by weight: 30-60 parts of methyl methacrylate, 10-20 parts of n-butyl acrylate, 10-30 parts of glycidyl methacrylate, 5-15 parts of styrene, 1-4 parts of a chain transfer agent, 1-5 parts of an initiator, and 30-50 parts of a solvent.
[0026] In terms of mass fraction, the raw material for preparing the acrylic resin in the embodiment of the present invention may include 30 to 60 parts of methyl methacrylate, specifically 30 parts, 35 parts, 40 parts, 45 parts, 48 parts, 50 parts, 53 parts, 55 parts, 56 parts, 58 parts or 60 parts. The role of the methyl methacrylate in the embodiment of the present invention is to improve the chemical corrosion resistance of the acrylic resin, make it more stable, suitable for more harsh environments, and help improve the transparency of the acrylic resin.
[0027] Based on the mass fraction of the methyl methacrylate, the raw material for preparing the acrylic resin in the embodiment of the present invention may include 10 to 20 parts of n-butyl acrylate, specifically 10 parts, 13 parts, 14 parts, 15 parts, 17 parts or 20 parts. The role of the n-butyl acrylate in the embodiment of the present invention is to improve the impact strength and ductility of the acrylic resin, thereby enhancing its mechanical properties.
[0028] Based on the mass fraction of the methyl methacrylate, the raw material for preparing the acrylic resin in the embodiment of the present invention may include 10 to 30 parts of glycidyl methacrylate, specifically 10 parts, 15 parts, 20 parts, 21 parts, 23 parts, 25 parts or 30 parts. The epoxy groups in the glycidyl methacrylate in the embodiment of the present invention can form a cross-linked structure through a curing reaction, thereby increasing the cross-linking degree of the acrylic resin and improving its mechanical strength and heat resistance.
[0029] Based on the mass fraction of the methyl methacrylate, the raw material for preparing the acrylic resin in the embodiment of the present invention may include 5 to 15 parts of styrene, specifically 5 parts, 8 parts, 9 parts, 10 parts, 12 parts or 15 parts. The styrene in the embodiment of the present invention can increase the interaction between polymer chains, thereby improving the rigidity of the acrylic resin.
[0030] Based on the mass fraction of the methyl methacrylate, the raw material for preparing the acrylic resin in the embodiment of the present invention may include 1 to 4 parts of a chain transfer agent, specifically 1 part, 2 parts, 3 parts or 4 parts. As an embodiment of the present invention, the chain transfer agent may be an aliphatic thiol and / or a disulfide; the aliphatic thiol may be dodecyl mercaptan; the dodecyl mercaptan may include n-dodecyl mercaptan and / or tert-dodecyl mercaptan.
[0031] Based on the mass fraction of the methyl methacrylate, the raw material for preparing the acrylic resin in the embodiment of the present invention may include 1 to 5 parts of an initiator, specifically 1 part, 2 parts, 3 parts, 4 parts or 5 parts. As an embodiment of the present invention, the initiator may be a peroxide initiator, and the peroxide initiator may specifically include one or more of di-tert-butyl peroxide, benzoyl peroxide, diisopropylbenzene peroxide and tert-butyl peroxy-3,5,5-trimethylhexanoate.
[0032] Based on the mass fraction of the methyl methacrylate, the raw material for preparing the acrylic resin in the embodiment of the present invention may include 30 to 50 parts of solvent, specifically 30 parts, 35 parts, 40 parts, 45 parts or 50 parts. As an embodiment of the present invention, the solvent may be an organic solvent, and the organic solvent may include one or more of xylene, ethylene glycol butyl ether, S-100 aromatic solvent, propylene glycol methyl ether acetate (PMA) and ethylene glycol ethyl ether acetate (CAC), for example, specifically xylene.
[0033] The method for preparing the acrylic resin in the embodiment of the present invention may include the following steps:
[0034] The raw materials for preparing the acrylic resin are mixed and polymerized to obtain the acrylic resin.
[0035] As an embodiment of the present invention, the mixing of the raw materials for preparing acrylic resin includes: heating part of the organic solvent separately, then adding the initiator solution and part of the monomer mixture, keeping warm, and finally adding the chain transfer agent and the remaining monomer mixture; wherein the initiator solution is obtained by pre-mixing the initiator and the remaining organic solvent, and the monomer mixture is obtained by pre-mixing methyl methacrylate, n-butyl acrylate, glycidyl methacrylate and styrene. As an embodiment of the present invention, the part of the organic solvent can account for 85-95% of the total mass of the organic solvent, specifically 90%; the temperature for heating part of the organic solvent separately can be 100-150°C, specifically 125°C. As an embodiment of the present invention, the initiator solution and part of the monomer mixture are added by dripping, the dripping time of the initiator solution can be 0.5-1h, the dripping time of the part of the monomer mixture can be 0.5-1h, and the initiator solution and part of the monomer mixture can be started to drip at the same time. As an embodiment of the present invention, the insulation time can be 0.5~1h; the remaining monomer mixture and the chain transfer agent are mixed and added in a dropwise manner, and the dropwise addition time can be 1~2h. As an embodiment of the present invention, the temperature of the polymerization reaction can be 140~180℃, specifically 140℃, 150℃, 160℃, 170℃ or 180℃; the insulation reaction time of the polymerization reaction can be 0.5~1h, and the insulation reaction time of the polymerization reaction of the present invention starts from the completion of the dropwise addition of the mixture of the remaining monomer mixture and the chain transfer agent. In the embodiment of the present invention, the reaction begins when the raw materials are added dropwise. The above mixing method can avoid the generation of a strong exothermic reaction, thereby improving the uniformity and repeatability of the product; the polymerization reaction under the above conditions can effectively control the molecular weight and molecular weight distribution of the polymer, which is conducive to obtaining an acrylic resin with excellent performance. As an embodiment of the present invention, the polymerization reaction can also include: vacuum distilling the obtained product system, and obtaining the acrylic resin after cooling; the present invention does not specifically limit the conditions of the vacuum distillation, and the conditions familiar to those skilled in the art can be used.
[0036] In an embodiment of the present invention, the curing agent may include one or more of dicyandiamide, dicarboxylic acid dihydrazide and dodecanedioic acid, and may specifically be dodecanedioic acid.
[0037] In an embodiment of the present invention, the auxiliary agent may include an anti-caking agent, a surface conditioning agent, an antioxidant and an ultraviolet absorber, and the mass ratio of the anti-caking agent, the surface conditioning agent, the antioxidant and the ultraviolet absorber may be 0.2~0.8:0.2~0.8:0.5~1.5:0.5~1.5, and further may be 0.4~0.6:0.4~0.6:0.8~1.2:0.8~1.2, and specifically may be 0.5:0.5:1:1. The anti-caking agent in the embodiment of the present invention may include one or more of fumed silica, nano-alumina and nano-titanium dioxide, and specifically may be fumed silica. The surface conditioning agent in the embodiment of the present invention may include benzoin and / or a modified polyamide wax type smoothing degassing agent, and specifically may be benzoin. In the embodiment of the present invention, the antioxidant may include one or more of a hindered phenol antioxidant, a phosphite antioxidant and a lactone antioxidant, and may specifically be a hindered phenol antioxidant; the hindered phenol antioxidant may be, for example, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester (antioxidant 626); the phosphite antioxidant may be, for example, bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite; the lactone antioxidant may be, for example, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester. The ultraviolet absorber described in the embodiment of the present invention may include one or more of o-hydroxybenzophenone, 2-(2H-benzotriazole-2-yl)-p-cresol and 2-[2-hydroxy-4-[3-(2-ethylhexyloxy)-2-hydroxypropoxy]phenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, and specifically 2-[2-hydroxy-4-[3-(2-ethylhexyloxy)-2-hydroxypropoxy]phenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine.
[0038] The present invention mixes acrylic resin, curing agent and auxiliary agent for extrusion to obtain extruded resin. The present invention does not specifically limit the mixing method of the acrylic resin, curing agent and auxiliary agent, and the components can be mixed evenly. In an embodiment of the present invention, the acrylic resin, curing agent and auxiliary agent are specifically placed in a high-speed mixer, mixed for 10 to 30 minutes at a rotation speed of 500 to 1000 rpm, and further mixed for 20 minutes at a rotation speed of 80 rpm. In an embodiment of the present invention, the extrusion temperature can be 50 to 110°C, specifically 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or 110°C; the main engine speed can be 40 to 200 rpm, specifically 40rpm, 60rpm, 80rpm, 100rpm, 120rpm, 140rpm, 160rpm, 180rpm or 200rpm; in an embodiment of the present invention, the mixture of acrylic resin, curing agent and auxiliary agent is specifically placed in an extruder for extrusion to obtain an extruded resin. In the embodiment of the present invention, the particle size of the extruded resin may be 120-200 μm.
[0039] After obtaining the extruded resin, the present invention mixes the extruded resin with organic flash powder for lamination to obtain the lightweight front plate of the photovoltaic module. In an embodiment of the present invention, the mass of the organic flash powder can be 0.1-2.5% of the mass of the extruded resin, specifically 0.1%, 0.3%, 0.5%, 0.7%, 1%, 1.3%, 1.5%, 1.7%, 2%, 2.3% or 2.5%, which can be adjusted according to the depth of the desired color. In an embodiment of the present invention, the particle size of the organic flash powder can be 10-200 μm, specifically 68-200 μm. In an embodiment of the present invention, the color of the organic flash powder can be blue-purple or red-yellow-green. In an embodiment of the present invention, the organic flash powder can include T80-607 and / or T80-134.
[0040] In an embodiment of the present invention, the lamination temperature can be 130~180℃, specifically 130℃, 140℃, 150℃, 160℃, 170℃ or 180℃; the pressure can be 0.1~1MPa, specifically 0.1MPa, 0.2MPa, 0.4MPa, 0.6MPa, 0.8MPa or 1.0MPa; the insulation and pressure holding time can be 30~60min, specifically 30min, 40min, 45min, 50min or 60min.
[0041] The present invention provides a photovoltaic module lightweight front plate prepared by the preparation method described in the above technical solution. In an embodiment of the present invention, the thickness of the photovoltaic module lightweight front plate prepared by the above method can be 300-500 μm, specifically 300 μm, 350 μm, 400 μm, 450 μm or 500 μm.
[0042] The present invention provides the application of the lightweight front plate of the photovoltaic module described in the above technical solution in solar photovoltaic power generation. The present invention does not specifically limit the specific application method of the lightweight front plate of the photovoltaic module, and the method familiar to those skilled in the art can be adopted. The lightweight front plate of the photovoltaic module provided by the present invention is widely used in the fields of photovoltaic power generation equipment manufacturing, architectural decoration design, etc. First, for the field of photovoltaic power generation equipment manufacturing, the lightweight front plate of the photovoltaic module described in the present invention can provide photovoltaic modules with more color options, meet the needs of different customers, and improve the market competitiveness of the product. Secondly, for the field of architectural decoration design, the lightweight front plate of the photovoltaic module described in the present invention can be designed according to the overall style and needs of the building to match the photovoltaic module, improve the overall aesthetics of the building, and achieve a perfect combination of photovoltaic power generation and architectural decoration.
[0043] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Preparation Example 1
[0045] The raw materials for preparing the acrylic resin are, by weight: 56 parts of methyl methacrylate, 14 parts of n-butyl acrylate, 21 parts of glycidyl methacrylate, 9 parts of styrene, 2 parts of a chain transfer agent (specifically n-dodecyl mercaptan), 1 part of an initiator (specifically di-tert-butyl peroxide), and 45 parts of a solvent (specifically xylene); the preparation method is as follows:
[0046] Methyl methacrylate, n-butyl acrylate, glycidyl methacrylate and styrene are mixed to obtain a monomer mixture; an initiator is mixed with a portion of xylene (accounting for 10% of the total mass of xylene) to obtain an initiator solution;
[0047] The remaining xylene (accounting for 90% of the total mass of xylene) is placed in a reaction container and heated to 125°C, and then the monomer mixture and the initiator solution are added dropwise at the same rate. After continuous addition for 0.5h, the initiator solution is added dropwise, and the temperature is kept for 0.5h. Then, the chain transfer agent is mixed with the monomer mixture that has not been added dropwise and continued to be added dropwise. After continuous addition for 2h, all materials are added dropwise, and the obtained reaction liquid is heated to 140°C and reacted for 0.5h. After the reaction is completed, the obtained product system is vacuum distilled and cooled to obtain the acrylic resin.
[0048] Example 1
[0049] The acrylic resin (from Preparation Example 1), the curing agent and the auxiliary agent are placed in a high-speed mixer, mixed at a rotation speed of 800 rpm for 20 minutes, and the obtained mixture is placed in an extruder, and extruded at an extrusion temperature of 100° C. and a main engine speed of 120 rpm to obtain an extruded resin (with a particle size of 120-200 μm); wherein the auxiliary agent is an anti-caking agent, a surface conditioning agent, an antioxidant and an ultraviolet absorber, and the mass ratio of the acrylic resin, the curing agent, the anti-caking agent, the surface conditioning agent, the antioxidant and the ultraviolet absorber is 76:20:0.5:0.5:1:1;
[0050] The extruded resin and the organic flash powder were mixed and placed in a hot press, and laminated for 50 minutes at a temperature of 140° C. and a pressure of 0.3 MPa to obtain a lightweight front plate of a photovoltaic module with a thickness of 360 μm.
[0051] Embodiment 2-4
[0052] The method of Example 1 is used, except that the amount of organic flash powder used is different. The raw materials for preparing the lightweight front plate of the photovoltaic module are listed in Table 1, and the proportions are listed in Table 2.
[0053] Comparative Examples 1 to 7
[0054] The method of Example 1 is referred to, except that no flash powder is added or inorganic flash powder is added, wherein some raw materials for preparing the lightweight front plate of the photovoltaic module are listed in Table 1, and the proportions are listed in Table 2.
[0055] Table 1 Some of the raw materials used in the examples and comparative examples
[0056]
[0057] Table 2 Formulas for preparing lightweight front sheets of photovoltaic modules in various embodiments and comparative examples
[0058]
[0059] Test Example 1
[0060] The performance of the lightweight front panels of photovoltaic modules prepared in the embodiments and comparative examples was tested, wherein the detection methods and test standards are listed in Table 3.
[0061] Table 3 Test Standards
[0062]
[0063] The performance test results of the lightweight front panels of photovoltaic modules prepared in various embodiments and comparative examples are shown in Table 4. As can be seen from Table 4, adding an appropriate amount of organic flash powder in the present invention can not only improve the color of the panel, but also has no effect on the light transmittance, and is beneficial to improving the water barrier performance; while adding inorganic flash powder has a great influence on the light transmittance, which seriously affects the power generation efficiency of the photovoltaic module.
[0064] Table 4 Test results of lightweight front sheets of photovoltaic modules prepared in various embodiments and comparative examples
[0065]
[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a lightweight front plate of a photovoltaic module, comprising the following steps: The acrylic resin, the curing agent and the auxiliary agent are mixed and extruded to obtain an extruded resin; The extruded resin is mixed with organic flash powder for lamination to obtain the lightweight front plate of the photovoltaic module, wherein the organic flash powder is T80-607 and / or T80-134, and the mass of the organic flash powder is 0.1-2.5% of the mass of the extruded resin; The mass ratio of the acrylic resin, curing agent and auxiliary agent is 72-76:19-23:1-5; The acrylic resin comprises the following raw materials in parts by weight: 30-60 parts of methyl methacrylate, 10-20 parts of n-butyl acrylate, 10-30 parts of glycidyl methacrylate, 5-15 parts of styrene, 1-4 parts of a chain transfer agent, 1-5 parts of an initiator, and 30-50 parts of a solvent.
2. The preparation method according to claim 1, characterized in that: The lamination temperature is 130-180° C., the pressure is 0.1-1 MPa, and the heat preservation and pressure holding time is 30-60 min.
3. The preparation method according to claim 1, characterized in that: The chain transfer agent is aliphatic thiol and / or dithioester; the initiator is a peroxide initiator.
4. The preparation method according to claim 1 or 3, characterized in that: The extrusion temperature is 50-110° C., and the main engine speed is 40-200 rpm.
5. A lightweight front plate for a photovoltaic module prepared by the preparation method according to any one of claims 1 to 4.
6. Application of the lightweight front plate of the photovoltaic module according to claim 5 in solar photovoltaic power generation.
Citation Information
Patent Citations
Solar photovoltaic high-weather-resistance transparent front plate packaging material and preparation method thereof
CN114134714A